2021
DOI: 10.2174/1570161119666201120160619
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Conditioning of the Heart: An Overview of Cardioprotective Signaling Pathways

Abstract: : Since the discovery of ischemic pre- and post-conditioning, more than 30 years ago, the knowledge about the mechanisms and signaling pathways involved in these processes has significantly increased. In clinical practice, on the other hand, such advancement has yet to be seen. This article provides an overview of ischemic pre-, post-, remote, and pharmacological conditioning related to the heart. In addition, we reviewed the cardioprotective signaling pathways and therapeutic agents involved in the above-ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 332 publications
0
26
0
Order By: Relevance
“…Understanding the molecular mechanism of the infarctlimiting effect of angiotensin 1-7 depends on the answer to this question. It has been found that receptors providing cardiac tolerance to I/R (opioid, cannabinoid, bradykinin, and adenosine) are associated with G i/o -, G q -, and G 11 -proteins [23][24][25]. There is evidence suggesting that the Mas receptor is coupled to G 11protein [20].…”
Section: Angiotensin 1-7 Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the molecular mechanism of the infarctlimiting effect of angiotensin 1-7 depends on the answer to this question. It has been found that receptors providing cardiac tolerance to I/R (opioid, cannabinoid, bradykinin, and adenosine) are associated with G i/o -, G q -, and G 11 -proteins [23][24][25]. There is evidence suggesting that the Mas receptor is coupled to G 11protein [20].…”
Section: Angiotensin 1-7 Receptorsmentioning
confidence: 99%
“…It is reported that intravenous administration of angiotensin 1-7 (8 pmol/kg = 7.2 μg/kg) to rats promotes stimulation of JAK2, Akt, and PI3K in the rat myocardium [96]. These kinases provide cardiac tolerance to I/R [23]. Stimulation of Akt and PI3K occurs due to the activation of the Mas receptor, and the stimulation of JAK2 occurs due to the activation of the AT 1 receptor.…”
Section: The Signaling Mechanism Of the Cardioprotective Effect Of An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is also involved in death of cardiomyocytes during I/R of the heart [116,117]. Diazoxide and pinacidil inhibited apoptosis induced by oxidative stress in neonatal rat cardiomyocytes by H 2 O 2 [118].…”
Section: Katp Channels and Apoptosismentioning
confidence: 99%
“…Rupture of the cell membrane is observed not only at necrosis but also at pyroptosis [127,128], necroptosis [129,130], and ferroptosis [130]. There is evidence that pyroptosis and necroptosis are involved in I/R cardiac injury [117,127,131]. It could be hypothesized that the cardioprotective effect of KCOs could be mediated not only via inhibition of necrosis but also by inhibition of pyroptosis and necroptosis.…”
Section: Katp Channels Necroptosis Pyroptosis and Autophagymentioning
confidence: 99%